DAMPAK PENERAPAN PENGELOLAAN TANAMAN TERPADU (PTT) PADI SAWAH TERHADAP PRODUKSI, EFISIENSI, PENDAPATAN DAN KETAHANAN PANGAN RUMAHTANGGA PETANI DI PROVINSI BALI - , SUHARYANTO, SP, MP., Dr. Jangkung Handoyo Mulyo, M.Ec ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The background of this research is the tendency of the rice production shown leveling off with constraints of physical-biophysical and fluctuations in input-output prices that affect incomes and household food security of farmers. This study aims to analyze the impact of implementation ICM on ICM alumni and non-ICM alumni to: (i) the production of rice and the factors that influence it, (ii) the level of technical efficiency, economic efficiency and allocative efficiency, (iii) socioeconomic factors that influence to technical inefficiency, (iv) rice farm income and the factors that influence it and (v) the level of household food security at various levels. The research was conducted in Bali province for two cropping seasons in 2011 by using three districts i.e. Tabanan, Gianyar and Buleleng as a center of rice production. The sample size is 216 farmer households taken by stratified random sampling consisting of 122 ICM alumni farmers and 94 non-ICM alumni farmers. The analysis techniques used are : (i) Stochastic Production Frontier to estimate production, technical inefficiency, technical efficiency, allocative efficiency and economic efficiency, (ii) Unit Output Price Cobb-Douglass Profit Function to estimate income and (iii) Ordered logistic model to identify the factors which influence the level of household food security. The results showed that : (i) overall rice production is affected by farm size, quantity of seeds, N fertilizer, organic fertilizers, pesticides, labor, age of seed and rice production is higher in the dry season, legowo cropping systems, intermittent irrigation systems, apply of IPM, using of new HYV and ICM alumni (ii) the average of technical efficiency, allocative efficiency and economic efficiency of ICM alumni is higher than non ICM alumni, (iii) socio-economic factors that influence to technical inefficiency of rice are : farmers age, formal education, farming experience, number of plots, land owner status and ICM alumni, (iv) rice income is affected by land area, price of N fertilizer, P fertilizer prices, prices of pesticides, labor wage, technical efficiency and rice income is higher on ICM alumni, land owner and cultivated on dry season,(v) household food security level of farmers affected by education, family size, household income, household food reserves, the price of rice, instant noodles price and household food security level of ICM alumni is higher than non ICM alumni.